Review of Models/Theories Explaining Tax Compliance Behavior (Sains Humanika, 2014)
This study offers an overview of the theoretical foundations for explaining tax compliance behavior. The interest generated by the subject matter of tax compliance behavior has led to identification of several factors that are believed to influence individual tax compliance decision. These factors have been compressed into several models/theories providing insights into the subject matter. This study reviewed five prominent theories/models that have been used to explain compliance via- economic deterrence; socio-psychology; fiscal exchange; comparative treatment; and political legitimacy. The study noted that there is no ‘one model fits all’ for explaining tax compliance behavior, and further concludes that individual tax compliance is influenced by both economic and non-economic factors. As such, tax administrators as well as researchers on the subject matter should combine relevant models and incorporate these factors into developing effective tax systems.
Keywords: Tax; taxation; compliance behavior; models